2023
DOI: 10.3389/fpls.2023.1264283
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses of the citrus WRKY gene family involved in the metabolism of fruit sugars and organic acids

Mingfei Zhang,
Wen Lu,
Xinxia Yang
et al.

Abstract: Sugars and organic acids are the main factors determining the flavor of citrus fruit. The WRKY transcription factor family plays a vital role in plant growth and development. However, there are still few studies about the regulation of citrus WRKY transcription factors (CsWRKYs) on sugars and organic acids in citrus fruit. In this work, a genome-wide analysis of CsWRKYs was carried out in the citrus genome, and a total of 81 CsWRKYs were identified, which contained conserved WRKY motifs. Cis-regulatory element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 81 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…To further understand the possible regulatory pathways of citrus sugar metabolism, we analysed the co-expression of CsSPSs based on our previous study ( Zhang et al., 2023a ). The results showed that all four CsSPSs were in the blue module (4,871 genes), which was positively correlated with the total sugar content, and the expression levels of most genes in the blue module increased with fruit development ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…To further understand the possible regulatory pathways of citrus sugar metabolism, we analysed the co-expression of CsSPSs based on our previous study ( Zhang et al., 2023a ). The results showed that all four CsSPSs were in the blue module (4,871 genes), which was positively correlated with the total sugar content, and the expression levels of most genes in the blue module increased with fruit development ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%